Breaking Barriers : Female Entrepreneurs Who Cross Over to Male-Dominated Sectors - World Bank (World Bank, Washington, DC, 2022)
The report focuses on sectoral choice as one of the contributors to the gender gap in firm performance. It explores the difference in profits among female entrepreneurs who cross over into male-dominated sectors (MDS) compared to those who remain in traditionally female-concentrated sectors (FCS). The report provides a snapshot of the factors associated with being a female entrepreneur who crosses over to MDS, including the most salient cross-country ones that are associated with breaking into and surviving in these sectors. Based on this analysis, it offers evidence-based programs and policies which can support women to cross over into more profitable sectors and contribute to their business performance more generally. The studies in this report were conducted across three regions and in ten countries (Sub-Saharan Africa: Botswana, Uganda, Ethiopia, and Guinea, in Latin America and the Caribbean: Peru and Mexico, and in East Asia and Pacific: Cambodia, Lao People’s Democratic Republic (PDR), Vietnam, and Indonesia). The report also draws from the findings of the global multi-country future of business survey of entrepreneurs carried out through a social media platform.